2012
DOI: 10.2174/157488412799218806
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review on Infusion Reactions Associated with Chemotherapies and Monoclonal Antibodies for Metastatic Colorectal Cancer

Abstract: Objective: The objective of this systematic review is to summarize the literature to date on the rates of infusion reactions (IR) associated with chemotherapies and monoclonal antibody (mAb) drug therapies used for the treatment of metastatic colorectal cancer (mCRC) and the associated clinical and economic impact. Methods: This study searched Medline, Medline (R) In-Process, Embase and Cochrane Library databases for studies on IRs associated with chemotherapy and mAbs in mCRC patients from 2000-2011.Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 54 publications
2
17
0
Order By: Relevance
“…The results of this study updated and expanded upon the 2012 systematic literature review by Song et al Although narrative in nature, their review reported incidences for cetuximab ranging from 7.6%‐33% in clinical trials and 27%‐32% in observational studies. We observed IR incidences for cetuximab ranging from 0%‐33% in clinical trials and 0.65%‐32% in observational studies.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The results of this study updated and expanded upon the 2012 systematic literature review by Song et al Although narrative in nature, their review reported incidences for cetuximab ranging from 7.6%‐33% in clinical trials and 27%‐32% in observational studies. We observed IR incidences for cetuximab ranging from 0%‐33% in clinical trials and 0.65%‐32% in observational studies.…”
Section: Discussionsupporting
confidence: 61%
“…IR in response to anti‐EGFR mAb drugs generally occur far less frequently than other therapies, although the reported range of incidence is wide (0%‐33%) . These proportions have been reported to vary by drug, as the incidence of IR associated with cetuximab ranged from 7.6%‐33%, whereas the proportions associated with panitumumab ranged from 0%‐4% . The cetuximab label reports IR incidence as occurring in approximately 3% of patients, and the panitumumab label reports an incidence of approximately 1%…”
Section: Introductionmentioning
confidence: 99%
“…IRRs were observed in 76% of patients following the first infusion of single-agent imgatuzumab in a dose-escalation trial and have been reported with 7.6% to 33% of cetuximab infusions (4,7). As a fully human antibody, the incidence of infusion reactions with panitumumab is much lower (0%-4%; ref.…”
Section: Introductionmentioning
confidence: 99%
“…As a fully human antibody, the incidence of infusion reactions with panitumumab is much lower (0%-4%; ref. 7). Premedication with corticosteroids and/or antihistamines is mandated for the first infusion of cetuximab and recommended for subsequent cycles (8); similar recommendations are made for rituximab, alemtuzumab, and infliximab (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Unlike cetuximab, panitumumab does not mediate antibody-dependent cellular cytotoxicity and less often results in infusion reactions and anaphylactic reactions than cetuximab, because panitumumab is a fully humanized antibody. 5 Multiple in vitro, in vivo, and clinical trials have demonstrated that the efficacy of anti-EGFR monoclonal antibodies depends on lack of v-Ki-ras2 Kirsten rat sarcoma viral oncogene homolog (KRAS) mutation, 6 although recent clinical and laboratory observations may challenge the current knowledge and clinical implications of KRAS mutation and anti-EGFR efficacy. [7][8][9] These anti-EGFR monoclonal antibodies have been evaluated in patients with advanced CRC as first-line, second-line, or later lines of therapy and as either a single agent or in combined chemotherapy.…”
Section: Introductionmentioning
confidence: 99%